New species of Tetradiplosis (Diptera: Cecidomyiidae) inducing galls on Prosopis caldenia (Fabaceae) in Argentina - Martínez, Juan José; Corró-Molas, Bárbara; Alfonso, Graciela L. (Zootaxa, 2013)
Two new species of Tetradiplosis inducing galls on Prosopis caldenia are described from Argentina: Tetradiplosis panghitruz Martínez n. sp. and Tetradiplosis rayen Martínez n. sp. Tetradiplosis panghitruz induces multilocular galls on vegetative stems, whereas T. rayen induces unilocular galls containing multiple larvae on the rachis of the developing inflorescences. The adult male, female, pupa and larva are described and illustrated for both species. A key to the known species of the genus is provided.